Board Characteristics and Financial Performance of Companies from the Agency Theory Perspective - Lukman Lukman; Siti Ridloah; Hanina Humaira (Journal Of Social Science (JoSS), 2024)
This study aims to examine the director size, frequency of director meeting, female director, and independent commissioner on the firm financial performance. The population in this study are companies listed in the LQ45 index for the 2017-2020 period. In this study, purposive sampling selected 27 companies as a sample, with the number of observations as many as 108 observations. This study uses an analytical method that analyzes regression with a fixed-effect model approach and hypothesis testing. The results show that director size positively and significantly affected the firm financial performance. The female director negatively and significantly affected the firm financial performance, the frequency of director meeting and independent commissioner has no significant negative effect on the company's financial performance, while leverage and growth as control variables has no significant positive effect on the firm financial performance. Investors are advised to pay more attention to factors such as director size and female directors to be taken into consideration before investing. This study suggests that future researchers can use other proxies in measuring the firm financial performance, both from a financial perspective such as ROE and a market value perspective such as Tobin's Q. Further researchers are also advised to examine other factors related to the board characteristics.